Factor analysis applied to magnitude estimates of punishment Seriousness: Patterns of individual differences - McClelland, Kent A. (Journal of quantitative criminology, 1985)
This research makes use of factor analysis to locate important dimensions of individual differences in perceptions of legal punishments. A sample of 152 recently arrested persons provided magnitude estimates of the seriousness of several types and levels of punishment. A factor analysis of the data showed that the major dimensions of individual differentiation were in responses to (a) lengthy periods of imprisonment; (b) several punishments judged less serious, including short periods in jail or on probation; and (c) fines. Regressions of the factor scores on individual characteristics are reported, and the implications of the analysis for deterrence theory are discussed.